Efficacy of Intravenous Chlorothiazide for Refractory Acute Decompensated Heart Failure Unresponsive to Adjunct Metolazone. Issue 8 (21st July 2016) - Cardinale, Maria; Altshuler, Jerry; Testani, Jeffrey M.
Abstract : Study Objective: To assess the efficacy of intravenous chlorothiazide in patients with acute decompensated heart failure (ADHF) who were determined to be loop diuretic resistant and refractory to metolazone. Design: Retrospective cohort study with patients serving as their own controls. Setting: Large, academic, tertiary care hospital. Patients: Forty‐five patients with ADHF who had an inadequate response to high‐dose loop diuretics and then received at least one dose of oral metolazone 5 mg or greater (metolazone index dose) followed by at least one dose of intravenous chlorothiazide 500 mg (chlorothiazide index dose) if the response to metolazone was considered inadequate, according to the institutional protocol, between February 4, 2013, and February 28, 2015, were included. If multiple doses of metolazone were administered, the last dose given before the chlorothiazide index dose was considered the index dose; the metolazone index dose had to have been administered more than 2 hours before the chlorothiazide index dose. Measurements and Main Results: Data for a total of 90 diuretic doses (45 metolazone, 45 chlorothiazide) were included in the analysis. The median dose of loop diuretic in intravenous furosemide equivalents given over the 24‐hour period before the metolazone index dose was 400 mg. The average length of stay was 34.7 days, and in‐hospital mortality was 35.6% (16/45 patients). The primary end point of a net‐negative urine output of 500 ml or greater during the 12 hours after the index dose occurred in 42.2% (19/45 patients) and 35.5% (16/45 patients) for the chlorothiazide and metolazone doses, respectively (p=0.581). The median 12‐hour urine output following administration of metolazone was 810 ml (interquartile range [IQR] 866 ml) versus 1075 ml (IQR 940 ml) following administration of chlorothiazide (p=0.363). Compared with metolazone, the chlorothiazide doses did not result in an increase in urine output of at least 500 ml during the 12 hours following the dose relative to the 12 hours before the dose (31.1% vs 22.2%, p=0.754). No significant difference in achievement of net‐negative urine output of 500 ml or greater during the 12 hours following the chlorothiazide or metolazone dose was noted (42.2% for chlorothiazide vs 35.5% for metolazone, p=0.581). Conclusion: The addition of intravenous chlorothiazide did not result in improved diuresis in patients with ADHF determined to be refractory to loop diuretics and adjunctive oral metolazone.